(3GdbhdfLs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdMeO ddg hHYO , abO NGWHfi SjOfG GdCejQ GdLdjd HYKQI GdOhdI Yf Gdedc caGAI s
(3BNQgG (B:s
(3hJJbQi GdCeYGA HEUdGM ShA eRGLgG , hbO SHb PcQ LejY Pdc hEP bO GSJhajfG Gdbhd HMSH GdZQV s
(3JNJda ai NGJeJgG Yf GdfSNJjf GdSGHbJjfs
(3fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs